The Analysis of the Dynamics of International Perezhivanie Research based on Citespace (2009-2024) - Cao, Jiahui (Journal of Educational Research and Policies, 2024)
This paper takes 153 articles about Perezhivanie research published in international authoritative journals between 2009 and 2024 in Web of Science core database as data source, analyzing the core literature of international Perezhivanie research in the past 15 years with the help of Citespace. Some scientific knowledge graphs of international Perezhivanie research are drawen. Citespace was used to analyze the core literature of international Perezhivanie research in the past 15 years by graphping the scientific knowledge of international Perezhivanie research.The aim of this study is to explore the core areas of Perezhivanie research and the high academic impact literature in this field, analyzing the hot topics of Perezhivanie research through key lineage clustering. It is found that over the past 15 years, the hot topics of international Perezhivanie research mainly include the dialectical unity of cognition and emotion, and the combination with other topics, such as motivation and agency. The research methodology mainly uses qualitative analysis tools.The article concludes with an outlook on the direction of development of Perezhivanie research in the context of the artificial intelligence era, where research in the future can be conducted by using a combination of quantitative and qualitative research methods.